Evaluasi Pengujian Termal dan X-Ray Diffraction Material Ka0,5Na0,5NbO3 - Amalia Ma'rifatul Maghfiroh (Universitas Sultan Ageng Tirtayasa, 2020)
The structure of perovskite-based material contained in the niobate and titanate. The fabric was a perovskite crystal structure having the formula ABO3. Ferroelectric and piezoelectric materials had a perovskite structure. This material could store an electric charge, which was good because of the polarization resulting in a material that was a dielectric. Unleaded piezoelectric material, K0,5Na0,5NbO3 (KNN), was synthesized using reliable state methods. Synthesis was done by first setting up K2CO3, Na2CO3, and Nb2O5 as a base KNN system. Studies cover X-ray diffraction, thermal analysis TGA-DTA and lattice parameter analysis. From the TGA-DTA analysis obtained for KNN calcination temperature at 7000C for 2 hours can produce a single-phase ABO3 where A = (K, Na) and B = (Nb). Orthorhombic perovskite structure KNN material owned by P4mm space group with lattice parameters a = 3,572 Å; b = 3,570 Å; and c = 3,565 Å.